Physical and physiological attributes of wrestlers: An update - Chaabene, H.; Negra, Y.; Bouguezzi, R.; Mkaouer, B.; Franchini, E.; Julio, U.; Hachana, Y. (The Journal of Strength and Conditioning Research, 2017)
Wrestling is one of the oldest combat sports, disputed since the ancient Greek Olympic Games. This combat sport discipline has caught the attention of scientists since 1943 which is the date that matches the appearance of the first scientific research dealing with wrestling. The current short review aimed to summarize and critically analyze the scientific literature related to wrestling's physical and physiological attributes and to provide practical recommendations for testing/training together with new perspective and areas of future scientific research. Regardless of sex and wrestling styles, an optimal level of cardiorespiratory fitness is important to help sustaining effort throughout the duration of the match and to stimulate the recovery process between periods. With regard to the anaerobic power and capacity, the available studies were in agreement about their critical importance toward reaching high-level wrestling success since these variables have discriminated well between successful and less-successful wrestlers regardless of age, weight classes, and wrestling styles. Physical fitness parameters such as maximal dynamic strength, isometric strength, explosive strength, and strength endurance are closely related to high-level wrestling performance. However, flexibility level seems not to be one of the key fitness variables that help to reach high-level wrestling success. Overall, to achieve high-level wrestling performance, training should be directed to develop anaerobic power and capacity, aerobic power, maximal dynamic and isometric strength, explosive strength, and strength endurance.